Balancing Target Achievement and Key Performance Indicators in the Performance Appraisal of Microcredit Officers at Bank Rakyat Indonesia - Edy Permana Setyawan; Daryono Daryono (UM Purwokerto Press, 2026)
Performance management constitutes a strategic instrument through which banking organizations align corporate objectives with individual employee contributions. In an increasingly competitive banking environment, the effectiveness of performance appraisal systems plays a critical role in sustaining productivity and service quality (Armstrong, 2014). Bank Rakyat Indonesia (BRI), with its strong focus on the microfinance sector, relies on Mantri (microcredit officers) as the frontline in credit distribution and micro-customer management (Megawaty, 2016). The performance appraisal of BRI’s Mantri is primarily based on the achievement of business targets, particularly loan disbursement, alongside the fulfillment of Key Performance Indicators (KPIs) encompassing both quantitative and qualitative dimensions (PT Bank Rakyat Indonesia, 2018). This study aims to evaluate the implementation of the Mantri performance appraisal system by examining the balance between target achievement and other KPI components. A qualitative case study approach was employed at one BRI unit, with data collected through in-depth interviews, direct work observations, and analysis of performance appraisal documents. The findings indicate that target achievement remains the dominant factor in Mantri performance evaluation. However, qualitative indicators such as Non-Performing Loan (NPL) levels, procedural compliance, and behavioral competencies significantly influence final performance ratings. These findings suggest that high target achievement alone does not guarantee superior performance appraisal outcomes when other KPI dimensions are not adequately fulfilled. Conversely, Mantri who slightly underperform in meeting targets but maintain strong credit quality and demonstrate sound professional behavior may still receive favorable evaluations. The study highlights the importance of balancing target-oriented and quality-oriented indicators to ensure sustainable and fair performance appraisal practices within BRI.